Un cinéma en travail ? À partir du film de Jean Rouch et d’Edgar Morin Chronique d’un été - Marc-Henri Piault (Images du Travail, Travail des Images)
By analysing Jean Rouch and Edgar Morin’s famous film, we can see one of the first expressions of awkwardness that is beginning to affect part of the youth and the working class. At the dawn of the 1960s, France was undergoing radical transformations marked by decolonisation, a massive rural exodus and the reconstruction of its cities and industries. Young people turned their back on the war and discovered pleasure, travel and the temptations of consumerism, but also the first doubts regarding progress and the Taylorian organisation of work. Thanks to its device that aims to give voice to them and thanks to the technological innovations of direct cinema, Chronique d’un été captures the signs of the ongoing mutations, which were asserted in particular in 1968. The two researchers/directors see in it a possible awareness, that of meeting the other without assimilating or dominating him.